The Efficacy of Photodynamic Inactivation of the Diode Laser in Inactivation of the Candida albicans Biofilms With Exogenous Photosensitizer of Papaya Leaf Chlorophyll - Astuty, Sri Dewi; Suhariningsih, .; Baktir, Afaf; Astuti, Suryani Dyah (Journal of Lasers in Medical Sciences, 2019)
Introduction: N Photodynamic inactivation has been developed to kill pathogenic microbes. In addition, some techniques have been introduced to minimize the biofilm resistance to antifungal properties in inhibiting cell growth. The principle of photodynamic inactivation different to antifungal drugs therapy which is resistant to biofilms. The presence of reactive oxygen species (ROS) that generating in photodynamic inactivation mechanisms can be damaging of biofilm cells and the principle of light transmission that could be penetrating in matrix layers of extracellular polymeric substance (EPS) until reaching the target cells at the base layers of biofilm. The present work aims to explore the potential of chlorophyll extract of papaya leaf as an exogenous photosensitizer to kill the Candida albicans biofilms after being activated by the laser. The potential of chlorophyll photosensitizer was evaluated based on the efficacy of inactivation C. albicans biofilm cell through a cell viability test and an organic compound test. Methods: The treatment of photoinactivation was administered to 12 groups of C. albicans biofilm for four days using the 445 nm laser and the 650 nm laser. The 445 nm and 650 nm lasers activated the chlorophyll extract of the papaya leaf (0.5 mg/L) at the same energy density. The energy density variation was determined as 5, 10, 20, 30 and 40 J/cm2 with the duration of exposure of each laser adjusted to the absorbance percentage of chlorophyll extract of the papaya leaf. Results: The absorbance percentage of chlorophyll extracts of the papaya leaf on wavelengths of 650 nm and 445 nm respectively were 22.26% and 60.29%, respectively. The most effective treated group was a group of the laser with the addition of chlorophyll, done by the 650 nm lasers with inactivation about 32% (P = 0.001), while the 445 nm lasers only 25% (P = 0.061). The maximum malondialdehyde levels by treatment of the laser 650 nm were (0.046±0.004) nmol/mg. Conclusion: The use of chlorophyll extract of the papaya leaf as a photosensitizer, resulted in the maximum spectrum of absorption at 414 nm and 668 nm, which produced a maximum reduction effect after photoinactivation up to 32% (with chlorophyll) and 25% (without chlorophyll). The utilization of chlorophyll extract of the papaya leaf would increase the antifungal effects with the activation by the diode laser in the biofilm of C. albicans. Keywords: Candida albicans biofilms; Chlorophyll extract; Photoinactivation